The role of digital marketing in increasing financial effectiveness and efficiency - Abdul Haris (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The primary objective of this study is to examine the effects of implementing digital marketing strategies on the financial performance of micro, small, and medium enterprises (MSMEs). The study analyzed data from multiple organizations incorporating digital marketing as a fundamental component of their company strategy. The research methodology employed in this study encompassed using surveys, examining financial data, and conducting interviews with business practitioners. The present study was born in the South Sulawesi Province, focusing on Medium, Small, and Micro Enterprises (MSMEs). The study's sample consisted of 100 participants. The data was thoroughly analyzed and tested in many ways, such as checking for validity and reliability and testing hypotheses using partial and coefficient of determination tests. The empirical evidence demonstrates that utilizing digital marketing strategies substantially impacts the efficacy and productivity of business financial operations. This study provides a significant contribution to the comprehension of the strategic use of digital marketing to enhance organizations' financial performance. The findings of this study have practical implications for enterprises, highlighting the importance of incorporating digital marketing into financial decision-making processes. To effectively navigate the dynamic digital business landscape, companies should design adaptive strategies to accommodate the ongoing changes in this domain.